Influence of calcination atmospheres on the physicochemical properties and catalytic activity of Ni1Co1Ox catalyst for CO oxidation. Issue 3 (6th March 2021) - Neha,; Prasad, R.; Singh, S. V.
Abstract: Nano‐Ni1 Co1 Ox spinel catalysts were prepared via a coprecipitation method, followed by calcination in different atmospheres (air, CO air, N2, and static air flow) tested CO oxidation in air. The calcination of basic cobalt‐nickel precursor in CO air mixture flow (4.5 vol.%) led to the formation of nano‐Ni1 Co1 Ox spinel with highest specific surface area, smallest crystallite size, porous, and well‐dispersed oxygen deficient structural defect morphology as revealed by N2 physiosorption, X‐ray diffraction (XRD), Fourier transform infrared (FT‐IR), and scanning electron microscopy–energy dispersive X‐ray analysis (SEM–EDX) results. The calcination in air and N2 flow improved the CO oxidation activity compared to calcination in static air. Though, the greatest activity was achieved with CO air calcined catalyst giving complete CO oxidation at 150°C.